MUSCULAR PSEUDOHYPERTROPHY (STEATOSIS) IN A BUFFALO CALF DELIVERED BY FETOTOMY - GHUMAN, S P S; HONPARKHE, M; SINGH, JAGIR (The Indian Journal of Animal Reproduction, 2023)
Muscular pseudohypertrophy of a localized region known as steatos is was observed in a ful I-term buffalo calfdelivered per-vaginum after fetotomy. Excessive enlargement of musculature of cervical and shoulder region ofright fore-limb was the cause of dystocia.
Keywords: Buffalo; Fetotomy; Muscular Pseudohypertrophy; Steatosis; Vaginal delivery